Effects of niobium doping site and concetration on the phase structure and oxygen permeability of Nb-substituted SrCoOx oxides - Zhang, K.; Ran, R.; Shao, Zongping; Zhu, Z.; Jin, Y.; Liu, Shaomin (Elsevier Science Ltd, 2010)
Niobium doping effect on phase structure, phase stability and electrical conductivity of SrCoOx oxides and oxygen permeability of the corresponding membranes were systematically investigated. Niobium was successfully incorporated into A-site, B-site or simultaneously A and B double sites of SrCoOx oxide and stabilized the perovskite structure with a cubic symmetry in air down to room temperature at a proper doping amount. However, the A-site doping could not stabilize the cubic structure under a more reducing atmosphere of nitrogen, as to SrCo1−yNbyO3−δ, y ≥ 0.1 is necessary to sustain the cubic perovskite structure. Simultaneous doping of Nb at A and B sites is the most effective way to stabilize the perovskite structure under nitrogen atmosphere. Irrespective of doping site, the electrical conductivity decreased monotonously with Nb-doping amount. Both NbxSr1−xCoO3−δ and NbzSr1−zCo1−zNbzO3−δ envisaged a decrease in oxygen permeation flux with Nb-doping amount while SrCo1−yNbyO3−δ reached the maximum flux at y = 0.1. Among all the membranes, SrCo0.9Nb0.1O3−δ and Nb0.05Sr0.95Co0.95Nb0.05O3−δ show the highest oxygen fluxes of 3.5 and 2.7 ml cm−2 min−1 at 900 °C under an air/helium gradient, respectively.